Vis ü Ramin Mesnevilerinde Kahramanların Özellikleri ve Aşk Anlayışları - Eğri, Sadettin (Kitabevi, 2001)
In this study two different versions of the same story, which had been written in Mesnevi genre, are compared in regard to the charecteristics of their personas and understanding of love. One of these versions is Fahrüddin Cürcânî's Vîs ü Râmîn .. The other one is Lâmi'î Çelebi's Vîse vü Râmîn. Cürcânî's Vîs ü Râmîn is quite different from other stories of love in many respects. Reflecting traces of ancient Persian creed and life, this work has also a considerable impact on Turkish Literature. Alımedi had first begun to translate this story. But, upon his death the translation remained incomplete. Lâmi'î Çelebi's Vîse vü Râmîn, on the other hand, was translated into Turkish in free meter as being highly different from its original form. Lâmi'î Çelebi added an Islamic and even a sophistic complexion to his version.
The Characteristic and Love Approaches of The Heroes in The Mesnevis of "Vis ü Ramin"
Keywords: Lami'î; Cürcânî; Vis/Veys; Râmîn; Mesnevi; Turkish Literature